1962
DOI: 10.1063/1.1733169
|View full text |Cite
|
Sign up to set email alerts
|

Power-Series Solutions for Energy Eigenvalues

Abstract: A numerical method is presented for rapidly calculating the energy eigenvalues of one-dimensional Schrödinger equations. It is applicable to systems for which the potential is either analytic or has no pole of order greater than two. The method is based on a power-series expansion of the wave function at large distances. With the use of high-speed computing machines the large number of terms required in the power series can be computed easily. The method is illustrated by obtaining energy eigenvalues for a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 5 publications
0
27
0
Order By: Relevance
“…The Padé method [10] is also an easy-to-use method which is more robust but less refined than the mapping method. The two methods (and also the analytic-continuation method [15,16]) may certainly be advantageously associated in the process of solving a two-point boundary problem of a nonlinear ODE. With M = 115, R = 6.03344983950017 and α = 2 the first odd state has been determined with 70 significant figures:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Padé method [10] is also an easy-to-use method which is more robust but less refined than the mapping method. The two methods (and also the analytic-continuation method [15,16]) may certainly be advantageously associated in the process of solving a two-point boundary problem of a nonlinear ODE. With M = 115, R = 6.03344983950017 and α = 2 the first odd state has been determined with 70 significant figures:…”
Section: Discussionmentioning
confidence: 99%
“…In that case Secrest et al [15] have suggested to reach the value z 0 in more than one step using the Taylor expansion about a non-zero value z l < z 0 . This suggestion is already the analyticcontinuation method introduced later on by Holubec and Stauffer [16].…”
Section: The Power-series Methodsmentioning
confidence: 99%
“…p͑x͒ ϭ 1 q͑x͒ ϭ Ϫ7x 2 ϩ 0.5x 3 ϩ x 4 w͑x͒ ϭ 0.5 a ϭ Ϫϱ LPN (36) * Morse potential [Secrest et al 1962]. (37) Quartic anharmonic oscillator [Scott et al 1969].…”
Section: Infinite Interval Singular: Lpn and Lcn-friedrichs Bcmentioning
confidence: 99%
“…The double-well potential problem and its generalizations have long been the object of several theoretical studies [1][2][3][4][5][6][7][8] in view of their importance as models for exchange forces, 2,3 and possible applications to real physical systems such as H 2 ϩ and NH 3 as well as models for H-bonding.…”
Section: Introductionmentioning
confidence: 99%